PKM KELOMPOK USAHA PARIWISATA UNTUK PENINGKATAN NILAI EKONOMI KAWASAN PANTAI BALONG MULYO - Rikah Rikah; Damayanti Damayanti; Ari Susanti (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2023)
The development of natural tourism in Rembang Regency is famous for its beaches, because Rembang Regency has a coastline of 60 km, this makes it worthy of being a coastal tourism icon. Through situation analysis, partner problems can be formulated: 1) Marketing that is not optimal, especially packaging of tourism products, 2) Tourism HR Management that lacks tourism-based knowledge. In connection with the above problems, the solution to overcome problems related to education-based tourism products is to provide training and assistance with tour package products, so that one of the outputs of this service program activity is a brochure for educational tour packages in the Balong Mulyo beach tourist area which includes four tourist attractions in the area. It is hoped that HR training activities for tourist attraction managers will increase HR knowledge regarding basic tourism knowledge. It is hoped that the implementation of this community service program will be able to support the increase in the number of visitors and partners' income as well as increase the economic value and welfare of the community in the Balong Mulyo Beach tourist area, Kragan.